Combinatorial neutron imaging methods for hydrogenation catalysts. Issue 44 (4th November 2022) - Nikolic, Marin; Longo, Filippo; Billeter, Emanuel; Cesarini, Alessia; Trtik, Pavel; Borgschulte, Andreas
Abstract : Combinatorial approach based on neutron imaging is capable of measuring more than 50 samples in situ under identical reaction conditions in one experiment. Abstract : Heterogeneous catalysts are materials with a complex structure at the atomic to mesoscopic scale, which depends on a variety of empirical parameters applied during preparation and processing. Although model systems clarified the general physical and chemical phenomena relevant to catalysis, such as hydrogen spillover, a rational design of heterogeneous catalysts is impeded by the sheer number of parameters. Combinatorial methods and high-throughput techniques have the potential of accelerating the development of optimal catalysts. We describe here a combinatorial approach based on hydrogen adsorption/absorption and hydrogen–deuterium exchange quantified by neutron imaging. The method coined CONI is capable of measuring more than 50 samples simultaneously. As a proof of concept, we study Pt catalyzed WO3 as an archetypal spillover system, and a Ni-catalyst supported on Al2 O3 and SiO2 . CONI is ideally suited to distinguish between irreversible surface adsorption and reversible bulk absorption, providing quantitative information. Concretely, CONI yields the number of reversibly adsorbed/absorbed hydrogen atoms in and on a great number of various catalysts in a single experiment.